1996
DOI: 10.1097/00005373-199605000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Biologic Activity of Tumor Necrosis Factor Maintains Vascular Endothelial Cell Function during Hyperdynamic Sepsis

Abstract: Since administration of PEG-(rsTNF-R1)2 maintains vascular endothelial cell structure and function, it can be concluded that TNF plays a pivotal role in producing endothelial dysfunction during sepsis. Thus, pharmacologic agents that inhibit TNF biologic activity and/or its production may be useful for protecting endothelial cells during sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Cellular damage is apparent as early as 15 min after LPS injection, with nuclear vacuolization, cytoplasmic swelling and protrusion, cytoplasmic fragmentation and detachment of the endothelium from its underlying layer. 33 In a caecal ligation and puncture rat sepsis model, similar events are seen after 10 h. 58 Circulating shed endothelial cells have also been identi®ed in human sepsis using antibodies to vWF and the VEGF receptor. 43 The number of circulating endothelial cells was higher in non-surviving patients than survivors.…”
Section: Infection and In¯ammationmentioning
confidence: 98%
“…Cellular damage is apparent as early as 15 min after LPS injection, with nuclear vacuolization, cytoplasmic swelling and protrusion, cytoplasmic fragmentation and detachment of the endothelium from its underlying layer. 33 In a caecal ligation and puncture rat sepsis model, similar events are seen after 10 h. 58 Circulating shed endothelial cells have also been identi®ed in human sepsis using antibodies to vWF and the VEGF receptor. 43 The number of circulating endothelial cells was higher in non-surviving patients than survivors.…”
Section: Infection and In¯ammationmentioning
confidence: 98%
“…Abnormal endothelial-dependent vascular relaxation is attributed to alteration of endothelial cell surface receptors, dysfunction of signal transduction pathways and downregulation and/or degradation of eNOS by pro-inflammatory cytokines such as TNF-, as well as by ROS/RNS or bacterial endotoxin [88]. In a model of septic shock, Wang et al [89] thus showed that inhibition of the biological activity of TNF-protects vascular endothelial cells' function. Finally, during sepsis, numerous stimuli potentially activate endothelium ATP-dependent potassium channels, like NO • or ONOO -, hypoxia, acidosis, or hyperlactatemia.…”
Section: Vasomotor Tone Abnormalitiesmentioning
confidence: 99%
“…As early as 15 min after LPS injection [7] cellular injuries are apparent, with nuclear vacuolization, cytoplasmic swelling and protrusion, cytoplasmic fragmentation, and various degrees of detachment of the endothelium from its underlying layer. This can also be observed 10 hours after the onset of sepsis in a caecal ligation and puncture rat model [8]. Proinflammatory cytokines increase permeability of the Ecs, and this is manifested approximately 6 hours after inflammation is triggered and becomes maximal over 12-24 hours as the combination of cytokines exert potentiating effects [8,9].…”
Section: Endothelial Injurymentioning
confidence: 99%
“…This can also be observed 10 hours after the onset of sepsis in a caecal ligation and puncture rat model [8]. Proinflammatory cytokines increase permeability of the Ecs, and this is manifested approximately 6 hours after inflammation is triggered and becomes maximal over 12-24 hours as the combination of cytokines exert potentiating effects [8,9]. Endothelial physical disruption allows inflammatory fluid and cells to shift from the blood into the interstitial space.…”
Section: Endothelial Injurymentioning
confidence: 99%